Go Diego Go! Bats to the Rescue! - Paz, Veronica; Mawhinney, Art; Contreras, Rosemary; Nick Jr. (Firm) (New York : Simon Spotlight/Nickelodeon, 2010)
It's Halloween and Diego and Alicia are throwing a party. Everyone's there, including Freddie the Fruit Bat. But where is Linda, the llama who's bringing the treats for the party?
"Based on the TV series Go, Diego, Go as seen on Nick Jr."--T.p. verso.
Accelerated Reader AR
Keywords: Márquez, Diego (Fictitious character) -- Fiction; Bats -- Fiction; Halloween -- Fiction; Parties -- Fiction; Llamas -- Fiction; Radio and television novels